PENINGKATAN KAPASITAS UMKM MELALUI PELATIHAN PENGAWETAN SAMBAL DALAM KEMASAN DI FORUM KOMUNIKASI USAHA MIKRO (FORSAMIK) CURUG, TANGERANG - Ratna Handayani; Yuniwaty Halim; W. Donald R. Pokatong; Beatrice Julian; Madeline Christabel Alexandra; M. Rifqi Nazuli; Christian Jeremy; Kenneth Kanovsky The (Universitas Mataram, 2026)
Forum Komunikasi Usaha Mikro (FORSAMIK) is an organization that oversees 238 members consisting of Micro, Small, and Medium Enterprises (MSMEs) at the sub-district level in Curug, Tangerang. Approximately 70% of these MSMEs operate in the food and beverage sector. Packaged chili sauce is one of the products developed by MSME members of FORSAMIK Curug, Tangerang. The main problem that is currently faced by these MSMEs is that the packaged sambal products they produce have a short shelf life, resulting in a sales system that depends solely on incoming orders. To increase production volume and expand the distribution reach to further improve the quality of packaged chili sauce products made by MSME members of FORSAMIK Curug, Tangerang, Food Technology team from UPH carried out this community service activity. The method used in this activity was active participation, consisting of observation, socialization, implementation, and evaluation stages. The activities were conducted in form of educational outreach and training. This community service was held on April 24, 2026, and was attended by 24 MSME representatives from Curug Sub-district, Tangerang. The activity received a positive response from participants, as indicated by their active participation throughout the sessions, increased knowledge based on the results of short quizzes conducted before and after the material delivery, and a strong willingness among participants to apply the knowledge gained at home and in their ongoing or future businesses. Through this activity, it is expected that the distribution reach of packaged sambal products will expand, ultimately improving the economic conditions of FORSAMIK Curug members.